Metode Pembiasaan Mendidik Anak dalam Perspektif Al-Ghazali dan Relevansinya di Era Modern - Mardliyah Mardliyah (Journal of Elementary Education Research, 2022)
Child education is a crucial aspect for the development of children in the future. Therefore, parents have the obligation to educate, teach and train their children to become happy individuals in this world and the hereafter. This shows that education has significant importance. One of the methods that can be used in educating children is the method of habituation according to Al-Ghazali. This method of habituation has high relevance with child education in the modern era. This study aims to explore Al-Ghazali's ideas about the urgency of the habituation method in educating children and its relevance in the modern era. This research is a literature review since the data were obtained from various literature sources that have relevance to the research. The method and approach used in this research are qualitative descriptive. The analysis used content analysis by analyzing the relevant text content with the research. The primary data sources are the books "Ihya' Ulumuddin" and "Ayyuhal Aulad," both of which are works of Al-Ghazali. Meanwhile, the secondary data sources include various books and journals relevant to the research. The research results show that Al-Ghazali's habituation method can help parents in shaping their children's good character and avoiding negative behavior. The habituation method in child education has significant meaning because it can determine whether a child can be good or bad. This habituation method is highly relevant in the modern era since children nowadays are more accustomed to using social media, which leads to negative behavior. Parents need to adapt the habituation method according to the needs and characteristics of their children while also considering environmental and social factors in the process of habituation. Therefore, the concept of Al-Ghazali's habituation method can be an alternative in educating children in the modern era.